2017
DOI: 10.1515/forj-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Country and regional carbon stock in forest cover – estimates based on the first cycle of the Czech National Forest Inventory data (2001–2004)

Abstract: Since forests can play an efficient role in the mitigation of greenhouse gas emissions, objective information about the actual carbon stock is very important. Therefore, the presented paper analysed the carbon stock in the living merchantable trees (with diameter at breast height above 7 cm) of the Czech forests with regard to groups of tree species and tree compartments (wood under bark with diameter above 7 cm, wood under bark with diameter below 7 cm, bark, green twigs, foliage, stump and roots). We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…However, they can represent (especially those from natural regeneration -usually very dense ones) considerable carbon flux to necromass. In the case of litter fall, the flux it may make up even larger amount than in old forests (compare our results with Merganič et al 2017). Analogously, young stands should not be omitted in forest carbon balance estimates at regional, country or any other levels.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, they can represent (especially those from natural regeneration -usually very dense ones) considerable carbon flux to necromass. In the case of litter fall, the flux it may make up even larger amount than in old forests (compare our results with Merganič et al 2017). Analogously, young stands should not be omitted in forest carbon balance estimates at regional, country or any other levels.…”
Section: Discussionsupporting
confidence: 56%
“…For instance, Pavlenda (2011) showed the annual foliage fall equaling about 320 g per m 2 in a middle-age beech and slightly over 100 g per m 2 in a middle-age spruce stand. Merganič et al (2017) estimated about 250 g of foliage annually shed per m 2 in the forests (prevailingly spruce) of the Czech Republic. Our previous studies (Barna et al -unpublished data) in an old beech stand showed the annual foliage fall between 300 and 400 g per m 2 .…”
Section: Discussionmentioning
confidence: 99%